Comparative Study on the Grain Refinement of Al-Si Alloy Solidified under the Impact of Pulsed Electric Current and Travelling Magnetic Field - Yunhu Zhang; Xiangru Cheng; Honggang Zhong; Zhishuai Xu; Lijuan Li; Yongyong Gong; Xincheng Miao; Changjiang Song; Qijie Zhai (Metals, 2016)
It is high of commercial importance to generate the grain refinement in alloys during solidification by means of electromagnetic fields. Two typical patterns of electromagnetic fields, pulsed electric currents (ECP) and traveling magnetic field (TMF), are frequently employed to produce the finer equiaxed grains in solidifying alloys. Various mechanisms were proposed to understand the grain refinement in alloys caused by ECP and TMF. In this paper, a comparative study is carried out in the same solidification regime to investigate the grain refinement of Al-7 wt. %Si alloy driven by ECP and TMF. Experimental results show that the application of ECP or TMF can cause the same grain refinement occurrence period, during which the refinement of primary Al continuously occurs. In addition, the related grain refinement mechanisms are reviewed and discussed, which shows the most likely one caused by ECP and TMF is the promoted dendrite fragmentation as the result of the ECP-induced or TMF-induced forced flow. It suggests that the same grain refinement process in alloys is provoked when ECP and TMF are applied in the same solidification regime, respectively.